Comorbidities associated with urinary tract infection by positive escherichia coli blee, in internal medicine service, Ate Vitarte Hospital. 2017 - 2018: Comorbilidades asociadas a infección de tracto urinario por Escherichia Coli Blee positivo del Hospital Vitarte. 2017 - 2018 - Chipa-Paucar, Yanina (2019)
Introduction: The infections by bacteria producing b-lactamasas extended spectrum (ESBL) are a serious problem in our country since the beginning of the year 2000 there has been a progressive increase in the frequency of infections caused by these bacteria, especially Escherichia coli and Klebsiella spp. Objective: To determine the comorbidities associated with patients with Urinary Tract Infection caused by e. colli BLEE of the Internal Medicine Service in the Vitarte Hospital in the period 2017-2018. Methods: Observational, case-control study. There was a sample corresponding to 114 divided into 57 cases and 57 controls. The information was collected through the review of medical records and the use of a data collection form. Descriptive statistics were used with measures of central tendency and dispersion, in the bivariate analysis the logistic regression, and in the multivariate analysis generalized linear models. Results: The median age of the population was 66.5 RI: 19-97 years, being 79.82% female (n = 23) and 46.49% mestizo (n = 53). In reference to those who had E. Coli BLEE, their age had a median of 64 years with RI: 19-97, and 43.48% (n = 10) of male sex had it as did 63.64% (n = 4) ) of those who had urinary obstruction, 55.56% (n = 5) of those who had urinary incontinence, 61.02% (n = 36) of those who had diabetes mellitus, 65% (n = 13) of the obese, 57.14% (n = 32) of the hypertensive patients and 62.71% (n = 32) of those who had recurrent UTI. It was determined in the bivariate analysis that DM (OR: 2.53, CI: 1.19-5.39, p = 0.016) and recurrent UTI (OR: 2.94, CI: 1.37-6.3, p = 0.005) were significant. In the multivariate analysis those who had recurrent UTI had 1.61 times the probability of having UTI of E. coli ESBL than those who did not have recurrent UTI with HF: 1.07-2.43, p = 0.022 adjusted for diabetes mellitus. Conclusion: Diabetes mellitus and recurrent UTI were comorbidities independently associated with UTI E. Coli BLEE, with recurrent UTI associated multivariate comorbidity adjusted for diabetes mellitus